Homophobia within schools of social work: the critical need for affirming classroom settings and effective preparation for service with the LGBTQ community. Issue 6 (17th August 2016) - Dentato, Michael P.; Craig, Shelley L.; Lloyd, Michael R.; Kelly, Brian L.; Wright, Caitlyn; Austin, Ashley
Abstract: Social work programs must effectively meet the needs of their diverse lesbian, gay, bisexual, transgender, and queer (LGBTQ) student populations as well as effectively train all students to work with minority groups including the LGBTQ community. While many undergraduate and graduate social work programs provide open, supportive, and affirming experiences for LGBTQ students, there remain ongoing challenges related to hostility, stigma, heterosexism, and homophobia within classroom settings across programs in the US and Canada. This study examines classroom experiences of homophobia among 1, 018 social work students. Qualitative data associated with three optional open-ended questions were analyzed utilizing grounded theory. Main qualitative findings identified several major themes associated with social work student experiences of homophobia in the classroom including: (1) Coming out ; (2) Faculty inaction ; (3) Implicit and explicit content ; (4) Direct language and actions ; and (5) Religious rationalizations and non - affirming positions. Conclusions and recommendations for social work education are discussed that center around creating safe and affirming classroom settings; the vital role of out faculty, students, and allies; impactful integration of diversity content within curricula, policies, and accreditation standards; ongoing training and mentorship; understanding the role of power and oppression; and a call to action among social work educators and the profession.